STRESS AND INADEQUATE FRUIT-VEGETABLE INTAKE AS MODIFIABLE RISK FACTORS FOR TYPE 2 DIABETES IN YOGYAKARTA: Stres dan Konsumsi Buah-Sayur Kurang sebagai Faktor Risiko Modifiable Diabetes Tipe 2 di Yogyakarta - Solikhah, Solikhah; Sulistiawan, Dedik; Matahari, Ratu; Rahmawati, Widya; Sarwani Sri Rejeki, Dwi (Jurnal Berkala Epidemiologi, 2025)
Background: Type 2 diabetes mellitus (T2DM) remains a significant global public health issue, with rising prevalence, including in Indonesia. At the same time, numerous studies have investigated modifiable risk factors of T2DM. To date, stress, fruit, and green-leafy vegetable consumption as risk factors of T2DM remain limited. Purpose: This study investigated the association between stress, fruit, and green-leafy vegetable consumption with T2DM occurrence among individuals under the supervision of Kalasan Public Health Center, Sleman, Yogyakarta. Methods: A cross-sectional study was conducted among 356 registered outpatients selected through purposive sampling. Stress levels were measured using the WHO Self-Reporting Questionnaire, while fruit and vegetable consumption was assessed using the Indonesia Basic Health Research 2018 questionnaire. T2DM status was determined based on fasting blood sugar levels recorded in medical records and confirmed by a physician's diagnosis. Results: Stress was linked to a higher probability of T2DM (Adjusted Odds Ratio (AOR)=2.61; 95% CI=1.25–5.44). Consuming fruit and green-leafy vegetables 2–3 times per week was associated with a lower likelihood of having T2DM (AOR=0.27; 95%  CI=0.13–0.56 and AOR=0.07; 95%CI=0.03–0.20, respectively). Conclusion: Stress increases the probability of T2DM. Fruit and green-leafy vegetable consumption 2-3 times per week was associated with a reduced likelihood of T2DM. These findings emphasize the need for targeted public health interventions promoting stress management and healthy dietary patterns strategies to mitigate T2DM risk in primary healthcare settings.